2003
DOI: 10.1021/cm034306r
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Low-Cost Preparation Method for Highly Dispersed PtRu/C Catalysts

Abstract: A low-cost impregnation method was developed to prepare PtRu catalysts highly dispersed on carbon support. As clearly revealed by the HRTEM image, even with high metal loadings (up to 40 wt % Pt + 20 wt % Ru) the average particle diameter was 1.5 nm with a narrow distribution ((0.5 nm). Based on EDAX, XRD, XPS, and TGA/DTA analyses, the structure of the PtRu catalyst was deduced to be composed of PtRu alloy and amorphous ruthenium compounds, predominantly hydrous ruthenium oxide, RuO x H y . The PtRu catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(94 citation statements)
references
References 82 publications
6
88
0
Order By: Relevance
“…However, several ppm of carbon monoxide (CO) present in the hydrogen (H 2 ) typically produced from reformation of natural gas, methanol or other liquid fuels, can severely poison the platinum active sites [1][2][3][4][5]7,[12][13][14]. Many studies have been carried out to develop CO-tolerant catalysts and considerable advances have been obtained [1][2][3][4][5][7][8][9][10][11][12][13][14]. Of many possibilities, the PtRu nanocomposites are now recognized as the most promising candidate [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several ppm of carbon monoxide (CO) present in the hydrogen (H 2 ) typically produced from reformation of natural gas, methanol or other liquid fuels, can severely poison the platinum active sites [1][2][3][4][5]7,[12][13][14]. Many studies have been carried out to develop CO-tolerant catalysts and considerable advances have been obtained [1][2][3][4][5][7][8][9][10][11][12][13][14]. Of many possibilities, the PtRu nanocomposites are now recognized as the most promising candidate [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of strategies for synthesis of PtRu bimetallic catalysts were attempted [1,[9][10][11]15]. Among these, chemical reduction methods, in which metal precursors are deposited on the surface of a support and then reduced to metal nanoparticles by introduction of a reducing agent, are commonly used [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies in the literature can be found dealing with platinum deposited on carbon (among others), [24][25][26][27][28] fundamental research on the preparation of carbon-supported platinum catalysts is rather scarce. 5,[29][30][31][32][33][34][35] In our research on the application of platinum on CNF, we have compared the results obtained with an HDP method with those obtained with ion adsorption (IA), and we have investigated the extent of interaction between the dissolved metal precursor and the CNF support.…”
Section: Introductionmentioning
confidence: 99%
“…Features of impregnation method are summarized in Table 1. [29][30][31][32][33][34] This method is widely used for preparing ORR catalysts; e.g., the carbon supported Pt and Pd nanoparticles. 35,36) As for the general procedures, it is as follows: the calculated amount of active metal precursor (e.g., H 2 PtC 16 x H 2 O, RuC 13 , Na 6 Pt(SO 3 ) 4 , and Na 6 Ru(SO 3 ) 4 ) is dissolved in a medium, such as alcohol and/or water.…”
Section: Synthesis Methods Of Catalystsmentioning
confidence: 99%
“…The carbon support loaded with the active metal precursor is then incubated in an oven at 100 o C overnight, and then treated with various reducing agents. Depending on the phase of the reducing agent, there are various methods including the hydrogen gas reduction method 31,32) and the liquid reduction method. 29,35,[38][39][40][41] Recently carbide based catalysts (e.g., Pt-W 2 C/C, Co 6 Mo 6 C 2 /C) prepared by combining the impregnation and microwave heating methods have been intensively studied.…”
Section: Synthesis Methods Of Catalystsmentioning
confidence: 99%